AN ANALYSIS ON THE ADVANTAGES OF COOPERATIVE LEARNING APPROACH IN TEACHING WRITING - Chamisah, Chamisah (Universitas Islam Negeri Banda Aceh, 2013)
This article aims to explain an analysis of cooperative learning approach advantages in teaching writing. Accordingly, learning writing by using cooperative learning makes the students easier in developing the ideas to write. This approach is more than just putting students into groups, but the students can work together, share information, and they are responsible for completion of the tasks in group as well. Besides, in this approach, the students can transfer their information and knowledge to the others and help each other in getting the ideas to develop in written communication during teaching-learning process.